An ANKRD26 nonsense somatic mutation in a female with epidermodysplasia verruciformis (Tree Man Syndrome). Issue 8 (5th June 2018) - Uddin, K. M. Furkan; Amin, Robed; Majumder, Sabbiha Nadia; Aleem, Mohammad Abdul; Rahaman, Atikur; Dity, Nushrat Jahan; Baqui, M. D. Abdul; Akter, Hosneara; Rahman, Muhammad Mizanur; Woodbury‐Smith, Marc; Scherer, Stephen; Uddin, Mohammed
Key Clinical Message: Epidermodysplasia verruciformis (EV) is an extremely rare hereditary skin disease characterized by an abnormal susceptibility to the human papilloma virus (HPV) with an increased risk of cutaneous malignancy. Here we report the first female severe EV case in Bangladesh, a 10‐year‐old girl with a nonsense somatic mutation impacting ANKRD26 gene. Abstract : Epidermodysplasia verruciformis (EV) is an extremely rare hereditary skin disease characterized by an abnormal susceptibility to the human papilloma virus (HPV) with an increased risk of cutaneous malignancy. Here we report the first female severe EV case in Bangladesh, a 10‐year‐old girl with a nonsense somatic mutation impacting ANKRD26 gene.